The Influence of Social Environment on the Understanding of Islam for Class X Students at Madrasah Aliyah Siompu Barat - Sakina, Nur; Darmayanti, Darmayanti; Sulasri, Sulasri (Journal of English Language and Education, 2026)
Understanding of Islamic Religion is often influenced by social interactions that occur between students and their families, schools, peers, and the surrounding community. Asy'arie, emphasized that strengthening Islamic Religious education in the educational environment has a significant impact on improving students' understanding of religious principles, moral values, and social behavior. This study aims to determine how the social environment influences students' understanding of Islamic religion. This study used a quantitative approach, with data analysis techniques, namely Pearson correlation analysis and determination coefficient test. The number of samples in this study was 57 respondents. Data collection techniques used a questionnaire. The results of the study explain that the social environment has a strong relationship with students' understanding of the Islamic religion, with the form of the relationship between these two variables being positive, which means that the higher the social environment, the higher the students' understanding of the Islamic religion. There is a positive and significant influence between the social environment on students' understanding of the Islamic religion. This is seen from the R square value = 0.612. Variable X influences variable Y by 61.2% while the remaining 38.8% is influenced by other factors.